Analysis of benzo[c]phenanthridine alkaloids in Eschscholtzia californica cell culture using HPLC-DAD and HPLC-ESI-MS/MS. Issue 7 (3rd July 2014) - Son, Seok Young; Rhee, Hong Soon; Lee, Min Woo; Park, Jong Moon
Abstract: Effective HPLC-DAD and HPLC-ESI-MS/MS methods have been developed for the analysis of eight benzo[ c ]phenanthridine alkaloids (sanguinarine, chelirubine, macarpine, chelerythrine, dihydrosanguinarine, dihydrochelirubine, dihydromacarpine and dihydrochelerythrine), which are important metabolites in Eschscholtzia californica cell culture. By adopting a ternary gradient pump system, the dihydro-form alkaloids hardly separable from each other could be successfully separated, and all the target alkaloids could be simultaneously quantified with the LOD values of 0.01–0.79 μg/mL and the LOQ values of 0.03–3.59 μg/mL. This HPLC-DAD method was further confirmed by HPLC-ESI-MS/MS system in multiple reaction monitoring mode. Each separated HPLC peak was identified as the target alkaloid, showing its relevant ionized molecule and selected fragment ion. By applying the established method, alkaloid production during the E. californica cell culture could be successfully monitored and some valuable information on its metabolism could be deduced. Graphical abstract: : HPLC-DAD and HPLC-ESI-MS/MS methods have been developed for the analysis of benzo[ c ]phenanthridine alkaloids and applied to Eschscholtzia californica cell culture monitoring.